2017
DOI: 10.1097/dcr.0000000000000729
|View full text |Cite
|
Sign up to set email alerts
|

Omission of Adjuvant Chemotherapy Is Associated With Increased Mortality in Patients With T3N0 Colon Cancer With Inadequate Lymph Node Harvest

Abstract: Patients with T3N0 colon cancer with inadequate lymph node harvest who receive adjuvant chemotherapy have increased overall survival. Despite this survival benefit, a fraction of these patients receive adjuvant chemotherapy. Barriers to chemotherapy are multifactorial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 19 publications
0
26
0
1
Order By: Relevance
“…The issue may be more than just an academic one, given that lymph node-negative pT3 tumors belong to a higher overall prognostic stage group compared with pT2 cases (IIA versus I) and may additionally benefit from adjuvant chemotherapy, particularly if they also fulfill certain high-risk criteria. [14][15][16][17][18][19] Therefore, we aimed to compare the clinicopathologic features and prognostic outcomes of this group of inconsistently staged tumors that seemingly exist as a histologic intermediary between the pT2 and pT3 categories. Our goal was to further define this diagnostically challenging subset of tumors and investigate whether their clinicopathologic characteristics and predictive behavior are more akin to pT2 or pT3 lesions, in order to further inform current staging guidelines as to their proper classification.…”
mentioning
confidence: 99%
“…The issue may be more than just an academic one, given that lymph node-negative pT3 tumors belong to a higher overall prognostic stage group compared with pT2 cases (IIA versus I) and may additionally benefit from adjuvant chemotherapy, particularly if they also fulfill certain high-risk criteria. [14][15][16][17][18][19] Therefore, we aimed to compare the clinicopathologic features and prognostic outcomes of this group of inconsistently staged tumors that seemingly exist as a histologic intermediary between the pT2 and pT3 categories. Our goal was to further define this diagnostically challenging subset of tumors and investigate whether their clinicopathologic characteristics and predictive behavior are more akin to pT2 or pT3 lesions, in order to further inform current staging guidelines as to their proper classification.…”
mentioning
confidence: 99%
“…Furthermore, AC is recommended in colon cancers of Stage II and higher with inadequate lymphadenectomy [3]. Wells et al [35] previously described low adherence to this recommendation, with AC use of only 36%. Our work supports this previously described disparity and highlights lymph node yield as an important pathological quality measure.…”
Section: Discussionmentioning
confidence: 99%
“…14 Omission of a single metastatic lymph node and leaving it with the patient can cause understaging and deprive patients of required adjuvant treatment which may increase survival. 15 Additionally, it has been shown that harvested lymph node numbers can be a denominator for recurrence and survival in patients with locally advanced (T3-T4) node-negative rectal cancer. 16 Although the American Joint Committee on Cancer and International Union Against Cancer recommended retrieval of at least 12 lymph nodes for staging of rectal cancer, 17 there are some studies that suggest to identify all the lymph nodes in each specimen and not to stop at 12.…”
Section: Discussionmentioning
confidence: 99%